2015
DOI: 10.1364/prj.3.000a64
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cascaded four-wave-mixing with graphene-coated microfiber

Abstract: A graphene-coated microfiber (GCM)-based hybrid waveguide structure formed by wrapping monolayer graphene around a microfiber with length of several millimeters is pumped by a nanosecond laser at ∼1550 nm, and multiorder cascaded four-wave-mixing (FWM) is effectively generated. By optimizing both the detuning and the pump power, such a GCM device with high nonlinearity and compact size would have potential for a wide range of FWM applications, such as phase-sensitive amplification, multi-wavelength filter, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…They also indicated that graphene might have large χ (3) nonlinearity due to its linear band structure allowing interband optical transitions at all photon energies. After that FWM was also observed in graphene-silicon hybrid optoelectronic devices [14] and graphenecoated microfiber [17,18]. Moreover, FWM-based wavelength conversion of a 10-Gb/s NRZ signal with mechanically exfoliated graphene was first reported in Ref.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…They also indicated that graphene might have large χ (3) nonlinearity due to its linear band structure allowing interband optical transitions at all photon energies. After that FWM was also observed in graphene-silicon hybrid optoelectronic devices [14] and graphenecoated microfiber [17,18]. Moreover, FWM-based wavelength conversion of a 10-Gb/s NRZ signal with mechanically exfoliated graphene was first reported in Ref.…”
Section: Discussionmentioning
confidence: 87%
“…After that, optical bistability, self-induced regenerative oscillations, and four-wave mixing (FWM) have been consecutively observed in graphene-silicon hybrid optoelectronic devices [14]. FWM has also been demonstrated in graphene in various configurations, e.g., slow-light graphene-silicon photonic crystal waveguide [15], graphene optically deposited onto fiber ferrules [16], and graphene-coated microfiber [17,18]. Moreover, FWM-based wavelength conversion of a 10-Gb/s non-return-to-zero (NRZ) signal with mechanically exfoliated graphene was first reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of massless Dirac fermions also lead to that the frequency of 2D plasmons in graphene scales as the electron density raised to 1/4, 13,14 in contrast to that of Schr€ odinger electrons 21,22 where the frequency of 2D plasmons scales as the square root of the electron density. Nonlinear photonics have important applications in graphene with respect to harmonic generation and nonlinear electrodynamic response, [23][24][25][26][27][28] broadband optical limiting application, 29 four-wave mixing frequency conversion, [30][31][32] nonlinear generation of plasmons, 33 and other applications. [34][35][36] The self-interaction among large amplitude 2D plasmons leads to harmonic generation, 37 and their sidebands could be an important source of instability and localization of wave energy.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that Dirac plasmons in graphene on SiC are hybridized with optical phonons of the SiC substrate [13], while scattering of plasmons off capillary waves (riplons) were observed in an electron sheet on liquid helium [1]. Nonlinear photonics have important applications in graphene with respect to harmonic generation [14], optical and plasmonic bistability [15,16], broadband optical limiting application [17], four-wave mixing frequency conversion [18], and other nonlinear photonic applications [19]. On the other hand, the self-interaction among large amplitude 2D plasmons and their sidebands could be an important source of instability and localization of wave energy.…”
Section: Introductionmentioning
confidence: 99%